1996
DOI: 10.1182/blood.v87.11.4879.bloodjournal87114879
|View full text |Cite
|
Sign up to set email alerts
|

Increased adhesion of erythrocytes to components of the extracellular matrix: isolation and characterization of a red blood cell lipid that binds thrombospondin and laminin

Abstract: Red blood cell (RBC) adhesion to the vascular endothelium is increased in several pathologic conditions, including sickle cell disease and malaria. However, RBC interactions with components of the subendothelial matrix are not well-characterized. Under in vitro flow conditions of 1 dyne/cm2, washed RBCs bound to the purified adhesive molecules thrombospondin (TSP) and laminin. Sickle RBCs had the greatest adhesion of all tested RBCs. The adhesion of sickle RBCs to immobilized TSP was inhibited by the anionic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(70 citation statements)
references
References 38 publications
6
57
0
5
Order By: Relevance
“…This hypothesis is supported by the increased adhesion of both NaCldehydrated and nystatin-dehydrated normal RBCs to TSP. In addition, inhibition of TSP adhesion to dehydrated normal RBCs with chondroitin sulphate A and high molecular weight dextran sulphate, but not chondroitin sulphate C, is similar to the inhibition of sickle RBC adhesion to TSP with the same treatments (Hillery et al, 1996). The mild augmentation of RBC adhesion upon pretreatment of dehydrated normal RBCs with the CD47 agonist peptide 4N1K parallels results with pretreatment of sickle RBCs with this peptide obtained by both our laboratory and others (Hillery et al, 1999;Brittain et al, 2001b).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This hypothesis is supported by the increased adhesion of both NaCldehydrated and nystatin-dehydrated normal RBCs to TSP. In addition, inhibition of TSP adhesion to dehydrated normal RBCs with chondroitin sulphate A and high molecular weight dextran sulphate, but not chondroitin sulphate C, is similar to the inhibition of sickle RBC adhesion to TSP with the same treatments (Hillery et al, 1996). The mild augmentation of RBC adhesion upon pretreatment of dehydrated normal RBCs with the CD47 agonist peptide 4N1K parallels results with pretreatment of sickle RBCs with this peptide obtained by both our laboratory and others (Hillery et al, 1999;Brittain et al, 2001b).…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with this behaviour, adhesion of NaCl-dehydrated (500 mOsM) or nystatin-dehydrated normal RBCs was also significantly (P < 0AE05, t-test) inhibited by pre-incubation of RBCs with HMWDS or CSA (Fig 4). In contrast, pre-incubation of RBCs with the related extracellular matrix polysaccharide CSC reduced, but did not significantly inhibit, dehydrated normal RBC adhesion to TSP (Fig 4), in agreement with similar findings with sickle RBCs (Hillery et al, 1996). When we further examined these data comparing the sickle, NaCltreated and nystatin-treated RBC groups using the Tukey method for multiple comparisons, we found that the sickle and nystatin-treated groups were significantly more inhibited by HMWDS compared with the NaCl-treated group.…”
Section: Inhibition Of Dehydrated Normal Rbc Adhesion To Tspsupporting
confidence: 89%
See 3 more Smart Citations